Improved physical properties and structural stability of value-added mayonnaises based on red palm olein by using high-shear homogeniser - Samsuri, N. S.; Abd Hadi, H. M.; Ismail Fitry, M. R.; Ab Karim, N. A.; Mat Yusoff, M. (Faculty of Food Science Technology, Universiti Putra Malaysia, 2022)
The present work formulated value-added mayonnaises based on red palm olein (RPOL) with improved physical properties and structural stability using a high-shear homogeniser (H-mayonnaise) as compared to the use of a lab-scale mixer (M-mayonnaise). The fat portions of the mayonnaises were blends of palm olein and RPOL at different ratios of 100:0, 75:25, and 50:50. The H-mayonnaises exhibited significantly smaller (p < 0.05) droplet size (448.95 - 515.61 vs 532.44 - 672.37 μm) and amount of separated oil (0.00 - 1.83 vs 16.83 - 42.68%) with more intact structure than M-mayonnaises. As the RPOL was increased from 0 to 50% (w/w), significant decrease (p < 0.05) was observed in the L* value (M-, 74.80 to 64.76; H-, 77.73 to 70.64), while both the a* (M-, -1.61 to 15.22; H-, -1.49 to 11.49) and b* (M-, 28.37 to 59.64; H-, 25.34 to 55.13) values increased in palm-based M- and H-mayonnaises. However, the fat portions had no significant effect on water activity, droplet size, and the amount of separated oil. All H-mayonnaises had higher storage modulus (G’ values), which highlighted greater mechanical rigidity and solid-like texture than M-mayonnaises. Different RPOL contents had no significant effect on the sensory acceptability of H-mayonnaises, except for the colour properties and overall acceptability. Overall, the physical properties and structural stability of RPOL-based mayonnaises were significantly improved by high-shear homogenisation relative to the use of a lab-scale mixer, while their sensory acceptance was comparable with mayonnaise prepared using soybean oil. Findings reported herein highlighted the potential development of mayonnaise based on RPOL for commercialisation purposes. There is also a potential for continuous demand of RPOL which could help to sustain its production, thus benefiting both the food and agricultural sectors.